2008
DOI: 10.1016/j.molcel.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

DAPK-ZIPK-L13a Axis Constitutes a Negative-Feedback Module Regulating Inflammatory Gene Expression

Abstract: Phosphorylation of ribosomal protein L13a is essential for translational repression of inflammatory genes by the interferon (IFN)-gamma-activated inhibitor of translation (GAIT) complex. Here we show IFN-γ activates a kinase cascade in which death-associated protein kinase-1 (DAPK) activates zipper-interacting protein kinase (ZIPK), culminating in L13a phosphorylation on Ser77, L13a release from the ribosome, and translational silencing of GAIT element-bearing target mRNAs. Remarkably, both kinase mRNAs contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(159 citation statements)
references
References 52 publications
3
156
0
Order By: Relevance
“…However, in a biological context the RNAbinding activity of RBPs is typically regulated by a plethora of mechanisms, including post-translational modifications (Mukhopadhyay et al 2008;Arif et al 2009), induced conformational changes (Walden et al 2006;Siddiqui et al 2012), competition with other RBPs for target RNAs (Yao et al 2012), differential subcellular localization (Alvarez et al 2013), alterations of its expression levels, or the availability of its target RNAs. Importantly, most of the proteins within the HeLa mRNA interactome are post-translationally modified (http://www.embl.de/mRNAinteractome) (Castello et al 2012), suggesting that RBPs may globally respond to environmental alterations.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a biological context the RNAbinding activity of RBPs is typically regulated by a plethora of mechanisms, including post-translational modifications (Mukhopadhyay et al 2008;Arif et al 2009), induced conformational changes (Walden et al 2006;Siddiqui et al 2012), competition with other RBPs for target RNAs (Yao et al 2012), differential subcellular localization (Alvarez et al 2013), alterations of its expression levels, or the availability of its target RNAs. Importantly, most of the proteins within the HeLa mRNA interactome are post-translationally modified (http://www.embl.de/mRNAinteractome) (Castello et al 2012), suggesting that RBPs may globally respond to environmental alterations.…”
Section: Discussionmentioning
confidence: 99%
“…10 It was further reported that DAPK3 regulates inflammatory signalings, including ribosomal protein L13a, extracellular signal-regulated kinase, and interferon-γ-activated inhibitor of translation in macrophages. 12 Vascular inflammation is known to be an important process for the development of hypertension at an early stage. In addition, a critical role for inflammation induced by ROS has been suggested in hypertension.…”
Section: Hypertensionmentioning
confidence: 99%
“…30 DAPK is also part of a negative-feedback module in regulating the expression of inflammatory genes. 31 Recent studies reveal an intriguing interplay between inflammasomes and autophagy. Caspase-1 activation suppresses Shigellainduced autophagy, 32 whereas autophagy inhibits activation of inflammasome.…”
Section: Introductionmentioning
confidence: 99%